Training on Podkeds to Improve Village Financial Management Competence in Kurungkambing Village - Solihat, Iis; Safitri, Julia; Sultan, Zulkifli; Juwita, Rakhmini; Norhamida, Hana (Help: Journal of Community Service, 2025)
Village fund allocations in Indonesia continue to increase each year, requiring village governments to strengthen their financial reporting capacity. Kurungkambing Village in Pandeglang Regency still faced difficulties in preparing accurate digital financial reports, particularly due to limited digital literacy and unfamiliarity with the Podkeds system. This community service program was designed to enhance the competencies of village officials in using Podkeds for transparent and accountable financial management. The program used a participatory training model consisting of needs assessment, workshops, hands-on practice, simulations using real financial data, mentoring sessions, and post-training evaluation. Participants included the village head, treasurer, administrative staff, and planning officers. Data were collected through observation, pre–post assessments, and documentation of Podkeds reporting outputs. The program improved participants’ technical competence in key Podkeds functions, such as data input, transaction recording, budget realization reporting, and monthly financial report generation. More than 80 percent of participants demonstrated increased mastery after mentoring. The use of Podkeds also reduced manual errors and shortened reporting time, supporting higher transparency and accountability in village finance. Findings indicate that digital training combined with guided mentoring can significantly enhance village financial governance. The improvement in digital skills and reporting accuracy reflects the importance of structured capacity-building programs for rural financial management. However, stable internet access and device availability remain challenges for sustainability. The Podkeds training program successfully strengthened the financial reporting skills of Kurungkambing Village officials. Continued technical assistance and infrastructure support are needed to maintain and expand the digitalization of village financial management.